The effects of problem based learning on mathematics performance and affective attributes in learning statistics at form four secondary level - Abdullah, Nur Izzati; Ahmad Tarmizi, Rohani; Abu, Rosini (Elsevier, 2010)
The challenge of globalisation today requires students to acquire problem solving and communication skills besides good procedural and conceptual knowledge of mathematics. This study was conducted to explore the effects of Problem Based Learning (PBL) as an alternative instructional strategy in the teaching and learning of mathematics effectively in Malaysian secondary schools. Previous research had discovered that that PBL enhances student's team work, problem solving skills and communication skills. In addition, interest in the subject significantly improved. A quasi experimental study with non-equivalent control group posttest only design was conducted to investigate the effects of PBL on form four Malaysian student's mathematics performance, instructional efficiency and affective attributes. The experiment was carried out for six weeks involving 53 Form Four students randomly selected from the district of Port Dickson. The experimental (PBL) group (n = 29) were exposed to the PBL instruction whereas the control (CT) group (n = 24) were taught conventionally. There were five instruments used in this study namely, mathematical learning worksheets, a posttest, Paas Mental Effort Rating Scale, a questionnaire on perception towards group work, interest in mathematics and perception towards mathematics learning experience and a rubric evaluating student's effective use of Polya's problem solving procedures, mathematical communication and teamwork. The data were analysed using analysis of covariance (ANCOVA) and independent t-test. student's response to the questionnaire and researcher's observations based on the rubric were described using means, standard deviations and percentages. The findings of the study indicated that PBL is just as efficient as the conventional teaching strategy in enhancing Form Four student's mathematics performance. Even though both groups of students showed positive perception towards group work, interest in mathematics and perception towards the learning experience they went through, the PBL group used the Polya's problem solving procedures more effectively, displayed better mathematical communication skills and showed stronger teamwork compared to the CT group.